A simulation study on the mechanical performance of natural fibre reinforced polymer composite material - Morshidi S.N.; Isa M.R.; Zaroog O.S. (American Institute of Physics Inc., 2023)
Natural fiber had recently been used as reinforcement with polymer in a composite is increasing, due to benefits. The benefits in natural fiber is the lightweight, low cost, environmentally friendly with a good specific mechanical property. However, several factors need to take into account to affecting the mechanical properties of natural fiber reinforced polymer, such as fiber fraction, fiber condition and fiber orientation. This study presents the simulation study on the mechanical properties of different natural fiber reinforced in a diagonal orientation and to compare the mechanical properties such as tensile and bending properties of Kenaf Fiber, PALF, and Ramie reinforced polymer composites. This study of mechanical properties will be investigated using ANSYS 18.1. The composites are designed in different natural fiber with fiber orientation in direction of 45 and 135 alternately in five layers. Tensile and bending test are analyze based on ASTM standard to determine the effect of stacking sequence and fiber orientation on the composites. The results show that fiber orientation have affect the mechanical properties of the composite materials. 2021 Author(s).